The Postnormal Times Reader - Sardar, Ziauddin (International Institute of Islamic Thought, 2023)
We live in a period of accelerating change. New trends, technologies and crisis emerge rapidly and transform familiar social and political landscapes. Established and cherished ideals, with deep historical roots, can be overturned overnight. Unconventional and uncommon notions and events can appear as though from nowhere, proliferate, and become dominant. The last few years alone have witnessed the emergence of populism and the far right in Europe and the US, Brexit, cracks in the European Union, cyber wars accompanied by the re-emergence of a cold war. China as an increasingly dominant new superpower. Pandemics like the Ebola and Zika viruses. Climate change leading to extreme weather events. Driverless cars. AI. ‘Fake News’. ‘Alternative Facts’. ‘Post-Truth’. ‘Disruptive technologies’ that disrupt and often corrupt everything. Everything seems to be in a state of flux, nothing can be trusted. All that we regard as normal is melting away right before us. The postnormal times theory attempts to make sense of a rapidly changing world, where uncertainty is the dominant theme and ignorance has become a valuable commodity. The Postnormal Times Reader is a pioneering anthology of writings on the contradictory, complex and chaotic nature of our era. It covers the origins, theory and methods of postnormal times; and examines a host of issues, ranging from climate change, governance, Middle East to religion and science, from the perspective of postnormal times. By mapping some of the key local and global issues of our transitional age, the Reader suggests a way of navigating our turbulent futures.